2007
DOI: 10.4269/ajtmh.2007.76.757
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox Zoonotic Associations: Insights From Laboratory Evaluation of Animals Associated With the Multi-State Us Outbreak

Abstract: At the onset of the 2003 US monkeypox outbreak, virologic data were unavailable regarding which animal species were involved with virus importation and/or subsequent transmission to humans and whether there was a risk for establishment of zoonotic monkeypox in North America. Similarly, it was unclear which specimens would be best for virus testing. Monkeypox DNA was detected in at least 33 animals, and virus was cultured from 22. Virus-positive animals included three African species associated with the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
161
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(190 citation statements)
references
References 22 publications
7
161
0
2
Order By: Relevance
“…Previous analyses demonstrated that realtime PCR detection of MPXV DNA was significantly more sensitive than detection of p.f.u. (Hutson et al, 2007). Therefore, specimens were first tested for the presence of orthopoxvirus DNA by PCR and, if positive, were subsequently evaluated for viable virus by tissue culture propagation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous analyses demonstrated that realtime PCR detection of MPXV DNA was significantly more sensitive than detection of p.f.u. (Hutson et al, 2007). Therefore, specimens were first tested for the presence of orthopoxvirus DNA by PCR and, if positive, were subsequently evaluated for viable virus by tissue culture propagation.…”
Section: Methodsmentioning
confidence: 99%
“…Human disease associated with West African MPXV infection is less severe and associated with less human-to-human transmission compared to Congo (Arita et al, 1985;Breman et al, 1980;Meyer et al, 2002), compared with up to 40 % for smallpox (Breman & Henderson, 2002). Human monkeypox had never been reported outside of Africa until 2003, when an outbreak occurred in the USA resulting from human contact with infected prairie dogs (PDs) which were co-housed with imported African rodents (Hutson et al, 2007;Reed et al, 2004). This outbreak demonstrated the potential for MPXV importation and, together with observations of ongoing human monkeypox in Africa (Boumandouki et al, 2007;Hutin et al, 2001;Learned et al, 2005;Meyer et al, 2002;Mukinda et al, 1997;Mwanbal et al, 1997;Rimoin et al, 2007), further emphasized the importance of a more complete understanding of this serious human pathogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first documented episode of human monkeypox outside the African continent occurred in 2003 in the Midwestern United States [92,[136][137][138][139][140]. The infection that occurred in the USA appeared to be milder than the disease described in the DRC.…”
Section: Persistence and Re-emergence Of Orthopoxviruses In Naturementioning
confidence: 96%
“…However, the possibility of reintroduction from an animal reservoir should be considered. If monkeypox virus could adapt to American native rodents such as rats, squirrels or prairie dogs, it will become a major public health concern regarding the potential for its establishment in novel reservoir species and ecosystems [78,92,138,140].…”
Section: Persistence and Re-emergence Of Orthopoxviruses In Naturementioning
confidence: 99%